Perancangan Sistem Informasi Penerimaan Peserta Didik Baru Pada SMA Tri Sukses Boarding School Kota Jambi Berbasis Website - Adryan Ryan; Admaja; Taufik Al Fahrazi (Jurnal Informatika Dan Rekayasa Komputer(JAKAKOM), 2023)
Information systems are very important for educational institutions to increase the competitiveness of schools with one another. The process of accepting new students at Tri Sukses Boarding School High School in Jambi City is still carried out by coming directly to school, this is not efficient both in terms of time, place, cost and energy. In addition, the preparation of new student acceptance reports is still being recapitulated using Microsoft Excel causing problems related to time and searching for new student data which is done one by one. From the existing problems, a system is needed to make it easier for prospective students to register. The system development method used is the Waterfall model, program modeling tools namely UML including use case diagrams, activity diagrams, and class diagrams. And the system is designed using the PHP programming language and MySQL database. This research resulted in a website-based new student admissions information system that can assist schools in managing new student admissions data.